The Impact of the COVID-19 Pandemic on Physician Visits in Japan - Kumagai, Narimasa (Frontiers in Public Health, 2021)
Background: Emerging from the coronavirus disease 2019 (COVID-19) scenario, fears of social distancing and contagion have led to a decline in the number of physician visits in Japan, placing severe financial strain on most hospitals and clinics. In this context, this study examined the impact of the spread of COVID-19 on the utilization of outpatient services. Methods: This study used monthly data drawn from the monthly statistics report of the social insurance medical fee payment fund in Japan and estimated fixed-effects models. Results: The results showed that the decline in the number of physician visits because of the first state of emergency declaration in Japan was greater than that caused by COVID-19’s spread during the same period. However, there was a decline in the impact of the declaration over time. After the second state of emergency declaration, the decline in the number of physician visits caused by the spread reduced by almost half. The nationwide preschool closure under the declaration of the first state of emergency also adversely impacted the number of physician visits. The reduced healthcare per capita costs of preschool children were greater among prefectures taking specific precautions. The results showed non-negligible regional differences in physician visits of preschool children during the sample period. Conclusions: The findings imply that we should not overestimate the negative impacts of the state of emergency declaration without lockdown on physician visits. To restore the number of physician visits to its pre-pandemic level, it is crucial to facilitate a smooth transition of COVID-19 patients between hospitals and an effective compensation program for hospitals with COVID-19 patients.